2021
DOI: 10.3389/fneur.2021.646293
|View full text |Cite
|
Sign up to set email alerts
|

Smiling, Yawning, Jaw Functional Limitations and Oral Behaviors With Respect to General Health Status in Patients With Temporomandibular Disorder—Myofascial Pain With Referral

Abstract: Background: The temporomandibular joint is the one of the most important joints in the human body. It enables numerous orofacial functions such as mastication, swallowing, breathing, speech, emotional communication, and facial expressions. The aim of the study was to evaluate the prevalence of jaw functional limitations and oral behaviors with respect to general health status in patients with temporomandibular joint disorders—myofascial pain with referral.Materials and methods: The study group consisted of 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
7
1
Order By: Relevance
“…As TMDs clearly affected jaw function in orthodontic patients, the first null hypothesis of this study was rejected. The mean scores of JLFS‐8 in PT patients were close to a previous study involving 50 patients with myofascial pain (mean JLFS‐8 score = 12.74 ± 12.48) 36 . Likewise, there are some studies showing PT patients have more severe mandibular movement limitation, 16,37 which is consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…As TMDs clearly affected jaw function in orthodontic patients, the first null hypothesis of this study was rejected. The mean scores of JLFS‐8 in PT patients were close to a previous study involving 50 patients with myofascial pain (mean JLFS‐8 score = 12.74 ± 12.48) 36 . Likewise, there are some studies showing PT patients have more severe mandibular movement limitation, 16,37 which is consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…found that healthy individuals had higher incisor biting symmetry in muscle organization (P < 0.03) than did patients with TMD. We found fewer verbal and emotional communication limitations than Kuć et al [20]. who studied 50 Polish patients with TMD who self-administered the JFLS, and reported di culty in smiling and in producing facial expressions and emotions.…”
Section: Mediation Analysis Between Anxiety and Jaw Functional Limita...contrasting
confidence: 46%
“…Although not all included psychological risk factors were found to be signi cant predictors of jaw functional limitation in multiple regression analysis, we cannot ignore the potential impact of these factors on jaw function. Kuć et al [20] constructed a multiple regression model with the GAD-7 score as the outcome variable and identi ed the PHQ-15 and PHQ-9 scores as signi cant predictors. These studies showed that psychological risk factors, such as depression, anxiety, somatization, sleep quality, and oral behaviors, are interrelated and have a combined in uence on jaw function.…”
Section: Risk Factors For Jaw Functional Limitationsmentioning
confidence: 99%
“…As a dysfunction of multifactorial nature, myofascial pain with referral is always related with trigger points of the head and neck. This condition reflects a combination of sensory experiences, motor reactions, and autonomic symptoms, including local and referred pain [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health concerns which could affect the functioning of the masticatory muscles, • Metabolic diseases, • Medications (long-lasting intake in the past and at present). The study group was described in detail in previous publications [25][26][27].…”
mentioning
confidence: 99%